Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find the value of \(\frac{x^2}{yz} + \frac{y^2}{zx} + \frac{z^2}{xy}\) given that \(x + y + z = 0\), we can use algebraic manipulation and properties of symmetric polynomial expressions. Here's the detailed, step-by-step solution:
[tex]\[ \text{Let} \; S = \frac{x^2}{yz} + \frac{y^2}{zx} + \frac{z^2}{xy}. \][/tex]
First, let's manipulate the expression:
[tex]\[ S = \frac{x^2}{yz} + \frac{y^2}{zx} + \frac{z^2}{xy}. \][/tex]
Rewrite each fraction with a common denominator:
[tex]\[ S = \frac{x^3}{xyz} + \frac{y^3}{xyz} + \frac{z^3}{xyz}. \][/tex]
Combine the terms over a common denominator:
[tex]\[ S = \frac{x^3 + y^3 + z^3}{xyz}. \][/tex]
Given that \(x + y + z = 0\), we can use a known algebraic identity for the sum of cubes:
[tex]\[ x^3 + y^3 + z^3 - 3xyz = (x + y + z)(x^2 + y^2 + z^2 - xy - yz - zx). \][/tex]
Since \(x + y + z = 0\), the identity simplifies:
[tex]\[ x^3 + y^3 + z^3 - 3xyz = 0. \][/tex]
Therefore, we have:
[tex]\[ x^3 + y^3 + z^3 = 3xyz. \][/tex]
Substituting this result back into our expression for \(S\):
[tex]\[ S = \frac{x^3 + y^3 + z^3}{xyz} = \frac{3xyz}{xyz}. \][/tex]
Simplify the fraction:
[tex]\[ S = 3. \][/tex]
Thus, the value of \(\frac{x^2}{yz} + \frac{y^2}{zx} + \frac{z^2}{xy}\) is:
[tex]\[ \boxed{3}. \][/tex]
[tex]\[ \text{Let} \; S = \frac{x^2}{yz} + \frac{y^2}{zx} + \frac{z^2}{xy}. \][/tex]
First, let's manipulate the expression:
[tex]\[ S = \frac{x^2}{yz} + \frac{y^2}{zx} + \frac{z^2}{xy}. \][/tex]
Rewrite each fraction with a common denominator:
[tex]\[ S = \frac{x^3}{xyz} + \frac{y^3}{xyz} + \frac{z^3}{xyz}. \][/tex]
Combine the terms over a common denominator:
[tex]\[ S = \frac{x^3 + y^3 + z^3}{xyz}. \][/tex]
Given that \(x + y + z = 0\), we can use a known algebraic identity for the sum of cubes:
[tex]\[ x^3 + y^3 + z^3 - 3xyz = (x + y + z)(x^2 + y^2 + z^2 - xy - yz - zx). \][/tex]
Since \(x + y + z = 0\), the identity simplifies:
[tex]\[ x^3 + y^3 + z^3 - 3xyz = 0. \][/tex]
Therefore, we have:
[tex]\[ x^3 + y^3 + z^3 = 3xyz. \][/tex]
Substituting this result back into our expression for \(S\):
[tex]\[ S = \frac{x^3 + y^3 + z^3}{xyz} = \frac{3xyz}{xyz}. \][/tex]
Simplify the fraction:
[tex]\[ S = 3. \][/tex]
Thus, the value of \(\frac{x^2}{yz} + \frac{y^2}{zx} + \frac{z^2}{xy}\) is:
[tex]\[ \boxed{3}. \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.